Implementation of Project-Based Entrepreneurship Learning for Students at the Muhammadiyah Cikampek Industrial Technology Vocational High School - Ulung, Guntur Syahputra; Kuat, Tri; Sayuti, Muhammad (CV. Publikasi Indonesia, 2026)
This study aims to analyze the implementation of project-based entrepreneurship learning in vocational high schools (SMK), specifically SMK Teknologi Industri Muhammadiyah Cikampek. The focus of the study includes the implementation of project-based entrepreneurship learning, the obstacles encountered in its implementation, and the solutions implemented to improve learning effectiveness. This study used a qualitative approach with a case study design. The research subjects included the principal, the vice principal for curriculum, the entrepreneurship teacher, and eleventh-grade students. Data were collected through in-depth interviews, passive participant observation, and documentation. Data analysis employed the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing and verifying conclusions. The results indicate that project-based entrepreneurship learning has not yet been fully implemented optimally. Learning remains dominated by theoretical approaches, although efforts have been made to introduce entrepreneurship projects such as product creation and business simulations. The main obstacles faced include limited facilities and infrastructure, insufficient learning time, and teachers’ limited competence in designing project-based learning. Solutions implemented by the school include increasing support for curriculum policies, providing training for entrepreneurship teachers, and strengthening collaboration between the school and students. This research provides theoretical contributions to the development of a project-based entrepreneurship learning model in vocational high schools, as well as practical implications for schools and teachers in improving the quality of entrepreneurship education to make it more applicable and contextual.